The Implications of Criminal Responsibility on Law Enforcement Officers in Cameroon: Sanctions and Enforcement Mechanisms - Ayuketang Brandon Eta (Studies in Law and Justice, 2024)
Let me be clear-no one is above the law. Not a politician, not a priest, not a criminal, not a police officer. We are all accountable for our actions. Over the past years, Cameroon has witnessed an increase in misconducts committed by Law Enforcement Officers especially in the Far North, North-West and South-West Regions. This has caused the government to take drastic measures in ensuring that they are accountable before the law. The State of Cameroon has put in place legal, policy and institutional frameworks as well as administrative platforms to sanction such Officers. These notwithstanding, the abusive functions of some officers have regrettably gained grounds at an alarming rate in Cameroon. This paper therefore dwells on the judicial and administrative sanctions which can be meted against recalcitrant Law Enforcement Officers in Cameroon. This paper does so through accessing some legal frameworks, court decisions, administrative acts taken by the Minister Delegate at the Presidency in charge of Defense, Delegate-General of National Security and other persons in authorities having control over these officers. The data thus collected constitutes the sources upon which this paper is founded. The findings revealed that the trial of these officers is basically hindered through the involvement of the executive amidst other factors. The findings equally reveal the dire need for the implementation of the penal laws. It recommends that there should be an independent body to police the investigation of crimes committed by them and thereby answering the question of who polices these officers, and the judiciary should be given free hand to act. All these is offered with the view of enhancing the criminal trial of Law Enforcement officers in Cameroon without hampering the smooth running of their duties.